Decolonising knowledge practices in biosecurity: Developing a reflective toolkit for more inclusive, equitable and respectful research - Susanna Finlay‐Smits; Maria Blanca Ayala; Will Allen; Andrea Grant; Alison Greenaway; Sara MacBride‐Stewart; Liz O'Brien; Katja‐Soana Ehler (People and Nature, 2025)
Abstract Context: Aotearoa New Zealand's biosecurity system, shaped by colonial and bureaucratic structures, tends to prioritise competition and financial management over environmental outcomes and community involvement. Successful biodiversity protection requires more cooperative, inclusive practices that engage local and Indigenous communities. Despite policies promoting knowledge sharing and collaboration, practical implementation remains a challenge. Approach: We took an action research approach, involving iterative cycles of inquiry, reflection and refinement to explore inclusive biosecurity practices. Through interviews and co‐analysis sessions with biosecurity professionals, including Māori researchers, we identified challenges and opportunities for integrating diverse knowledge systems. By synthesising empirical insights with theoretical frameworks, we co‐developed practical tools to address these challenges and promote more collaborative approaches in biosecurity research, policy and practice. Findings: We identified six dimensions of collective praxis to support those within the biosecurity system to work in a more inclusive, respectful, pluralistic and regenerative manner. Synthesis and application of findings: To help practitioners reimagine their work practices, we developed a rubric with reflective prompts and gave it a more convenient and user‐oriented format as a set of cards. These tools were designed to spark critical thinking and facilitate individual and collective self‐assessment and priority setting (when used as a planning device). These support devices are intended for people working at the nexus between different knowledge systems. They were designed to help people with diverse cultural, disciplinary and professional backgrounds work better together and critically reflect on everyday practices that marginalise, discredit or disempower ways of knowing and doing that differ from mainstream scientific biosecurity. Conclusion: This action research contributes towards decolonisation of the broader research culture, biosecurity system and biodiversity protection goals. The process is also valuable in adapting to changing contexts and highlights the power of reflection in reframing practices across a wide range of situations, beyond biosecurity, to foster collaboration and ensure more equitable decision‐making. Read the free Plain Language Summary for this article on the Journal blog.